Vplyv prípravkov určených na dezinfekciu kože, slizníc a rán na životaschopnosť biofilmovej formy rastu mikroorganizmov izolovaných od pacientov s katétrovými infekciami - Slobodníková, L; Hupková, H; Koreň, J; Záborská, M (Epidemiologie, mikrobiologie, imunologie, 2014)
AIM OF THE STUDY: To evaluate the activity of four disinfectious agents used for skin, mucosa and wound disinfection (chlorhexidine digluconate, povidone-iodine, octenidine hydrochloride, super oxygenated water) on the biofilm of Staphylococcus aureus, Escherichia coli and Candida sp. strains, isolated from patients with catheter-related infections. MATERIAL AND METHODS: The tested agents were applied on 24-hours biofilm in the microtiter plate wells. After 20-minutes exposition, the wells were washed, and the microbial vitality was tested by regrowth method after 24-hours cultivation in fresh culture medium. Biofilm formation was confirmed in a parallel microtiter plate; the quantity of produced biofilm was measured after crystal violet staining spectrophotometrically at 570 nm. RESULTS: All four tested disinfectious agents inactivated the biofilm of all S. aureus, E. coli, C. albicans, C. krusei and C. glabrata strains, without respect to the intensity of biofilm production. Three strains of C. tropicalis with intensive biofilm production partially preserved their vitality after exposition to chlorhexidine and povidone-iodine, and 2 strains to octenidine. Super oxygenated water had no effect on yeasts associated with massive biofilm of one C. tropicalis strain, and only partially decreased the vitality of additional two strains. CONCLUSIONS: The tested disinfectious agents proved in-vitro antibiofilm activity on all microbial strains from catheter-related infections, with exception of three C. tropicalis strains with intensive biofilm production. Octenidine was found to be the most active agent. The results enable to assume, that the tested disinfectious agents, when applied to patients, will inactivate not only the individual microorganisms not protected by biofilm, but also the biofilm on the catheter surfaces approachable by local application. However, C. tropicalis strains producing massive biofilm, protecting them partially from effects of disinfectious agents tested in the present study, still remain a challenge.
Keywords: mužské pohlaví; Male; Escherichia coli; dezinfekce; sliznice; rány a poranění; dezinficiencia; Humans; Skin; kůže; Candida; lidé; biofilmy; Disinfection; Staphylococcus aureus; Wounds and Injuries; Mucous Membrane; Disinfectants; Catheter-Related Infections; katétrové infekce; dospělí; Adult; Biofilms